Performance of Sharia Commercial Bank In Indonesia The Role Of Intellectual Capital And Islamicity Performance Index - Mais, Rimi Gusliana; Munir, Munir; Syafrinaldi, Zidan (Baca Dulu Publisher, 2025)
This study aims to determine the effect of Intellectual Capital and Islamicity Performance Index on the profitability of Islamic commercial banks in Indonesia with the panel data analysis method using Eviews 10. The sample is determined based on the purposive sampling method, with a total sample of 6 Islamic banks and produces 30 observation samples because it uses reports annual finances. The results of the study prove that Intellectual Capital, equitable distribution ratio and Islamic income vs. non-Islamic income ratio have no effect on profitability. while the profit sharing ratio and zakat performance ratio affect profitability. This study provides evidence that the performance of Islamic banking can be proven from various aspects, the variables used in this study are influential and some are not. The implications of this research for companies are expected to be complementary material and useful input and considerations for companies and readers are expected to see the results of this research as useful information material and can be used for the benefit of readers. This research has enormous value, it is hoped that Islamic banking can apply Islamic principles in its operational activities in this study, namely Intellectual Capital, PSR, ZPR, EDR, and IIR.